Integration of Blockchain Technology, Artificial Intelligence, and Machine Learning in Financial Accounting: Transformation Towards Efficiency and Transparency - Basu, Pooja; Jayadi, Usman (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2025)
The development of information technology has brought significant changes to the accounting world, particularly with the integration of blockchain technology, artificial intelligence (AI), and machine learning (ML). This article discusses the application of these three technologies in financial accounting, which has the potential to improve efficiency, transparency, and accuracy. Blockchain offers security and transparency in transaction recording, while AI plays a role in automating processes and detecting anomalies in financial data. Machine learning enables more accurate predictive analysis in financial planning and risk detection. Although challenges in implementation, such as regulatory issues and data quality, still exist, the potential benefits are enormous. The integration of these technologies can reduce human error, speed up the auditing process, and provide better financial management. This article also highlights the challenges faced in their application, including the need for adequate infrastructure and training. Overall, the use of blockchain, AI, and ML in accounting paves the way for a more efficient and transparent digital transformation in the accounting industry.